2014
DOI: 10.4172/2155-9880.1000352
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 and Atherosclerosis: Mediator or Biomarker

Abstract: Atherosclerosis, a progressive disorder of the vessel walls with the formation of plaques throughout the arterial system, is an essential pathological process in the development of various Cardiovascular Diseases (CVDs). Inflammation has been demonstrated to play an inevitable role in all the stages of atherosclerosis though its pathogenesis is complicated and still remains enigmatic. Interleukin-18 (IL-18) is a pleiotropic pro-inflammatory cytokine, which belongs to the Interleukin-1 (IL-1) family. This pro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Cainzos-Achirica et al explored the prognostic value of IL-6 for the prediction of atherosclerotic cardiovascular disease (ASCVD) events, HF, and other chronic diseases in 6617 participants and concluded that IL-6 is strongly and independently associated with ASCVD events, HF, and all-cause mortality, particularly among statin users [53]. IL-18 is another promising prognostic marker for CAD [54]. Opstad at al.…”
Section: Inflammation Biomarkersmentioning
confidence: 99%
“…Cainzos-Achirica et al explored the prognostic value of IL-6 for the prediction of atherosclerotic cardiovascular disease (ASCVD) events, HF, and other chronic diseases in 6617 participants and concluded that IL-6 is strongly and independently associated with ASCVD events, HF, and all-cause mortality, particularly among statin users [53]. IL-18 is another promising prognostic marker for CAD [54]. Opstad at al.…”
Section: Inflammation Biomarkersmentioning
confidence: 99%
“…This cytokine is among the more recently recognized cytokines to be involved in the development of various cardiovascular diseases. At one end, studies indicate that IL-18 is a key player that orchestrates the inflammatory cascade associated with the pathogenesis of atherosclerosis whereas others show circulating IL-18 levels to be a prognostic marker [48].…”
Section: Interleukinesmentioning
confidence: 99%
“…Interleukin-18 (IL-18) is a pro-inflammatory cytokine with a critical role in the inflammation that adds to atherosclerosis [6]. Expanded levels of circulating IL-18 have been might be connected with quickening of atherosclerosis and H EART disease is impacted by ecological and inherited factors.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the IL-18 gene were connected with raised IL-18 serum focuses and higher cardiovascular mortality among CAD patients. Distinctive studies showed that IL18 polymorphisms are incorporated into the advancement of ischemic stroke [8], dead tissue [9], and higher cardiovascular mortality risk [6].…”
Section: Introductionmentioning
confidence: 99%